Modifikasi Headstega berdasarkan Penyisipan Karakter - Hasmawati Hasmawati; Ari Moesriami Barmawi (School of Computing, Telkom University, 2017)
AbstractHead steganography or Headstega is one of noiseless steganography paradigm, or Nostega.This method utilizes the email header as a media of message concealment. There are several problems that can be enhanced in Headstega, i.e. low embedding capacity and high level of suspicion. Modified Headstega based on Character Hiding uses a combination of consonant vowel to embed the secret messages into email address. The messages embedding process using four consonant vowel combination that represented one character in Indonesian language. From the experiments conducted, the results obtained that the Modified Headstega has a better performance than the Original Headstega in term of embedding capacity and also in suspicion level. Keyword : Steganography, Nostega, Headstega, Character Hiding